2011
DOI: 10.1155/2011/706262
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis Characterization and Biological Activity Study of New Schiff and Mannich Bases and Some Metal Complexes Derived from Isatin and Dithiooxamide

Abstract: Two new Schiff and Mannich bases, namely, 1-Morpholinomethyl-3(1′ -N-dithiooxamide)iminoisatin (LIH) and 1-diphenylaminomethyl-3-1′-N-dithiooxamide)iminoisatin (LIIH), were prepared from condensation reaction of new Schiff base 3-(1′-N-dithiooxamide)iminoisatin (SBH) with morpholine or diphenylamine respectively in presence of formaldehyde . The structures were characterized by IR, 1HNMR, mass spectrometry, and CHN analyses. Metal complexes of the two ligands were synthesized, and their structures were charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…On the other hand, Inorganic elements play crucial role in biological and biological medical processes, and it is evident that many organic compounds used in medicine do not have a purely organic mode of action, some of them are activated or bio transformed by metal ions metabolism. Many drugs possess modified toxicological and pharmacological properties in the form of metal complex and probably Schiff bases are versatile C=N (imine) containing compounds possessing broad spectrum of biological activity and incorporation of metals in the form of complexes showed some degree of antibacterial, antifungal, antitumor, anticancer and anti-inflammatory activity [4][5][6][7][8]. In vivo studies have indicated that some biologically active compounds may become more carcinostatic and bacteriostatic upon chelation [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Inorganic elements play crucial role in biological and biological medical processes, and it is evident that many organic compounds used in medicine do not have a purely organic mode of action, some of them are activated or bio transformed by metal ions metabolism. Many drugs possess modified toxicological and pharmacological properties in the form of metal complex and probably Schiff bases are versatile C=N (imine) containing compounds possessing broad spectrum of biological activity and incorporation of metals in the form of complexes showed some degree of antibacterial, antifungal, antitumor, anticancer and anti-inflammatory activity [4][5][6][7][8]. In vivo studies have indicated that some biologically active compounds may become more carcinostatic and bacteriostatic upon chelation [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…This is due to the coordination of the metal ion with the ligand. The spectra of complexes demonstrated new band vibrational modes to the M-N, M-S, and M-Cl group frequencies as a result of bonding the metal ion with the ligand L1Ni for νM-N 532, νM-S 422, and νM-Cl 337 as well as L1AgνM-N 532, νM-S 447, and L1Pd for νM-N 516, νM-S 400, and νM-Cl 333 [12], [18], [19], [20], [21], [22], [23]. The FTIR spectra for the compounds L1, L1Ni, L1Ag, and L1Pd are demonstrated in Figure 3.…”
Section: Infrared Spectra (Ft-ir) For the Free Ligand (L1) And Itsmentioning
confidence: 99%
“…The four heterocyclic ligands were attached to each of the four metal complexes. Only the copper complexes (57d) displayed potent cytotoxicity against Artemis salina (LD 50 Other new isatin-metal complexes include Schiff and Mannich base ligands coordinated to metal salts such as Co(II), Ni(II), Mn(II) and Ir(III) [141]. The complexes were evaluated against the Hep-2 larynx carcinoma cell line and the Ir(III) complex 58 (Fig.…”
Section: Metal Complexesmentioning
confidence: 99%